Preparation, modification and characterization of activated carbons for batch adsorption studies on the removal of selected metal ions - Adil, Mohammad (2006)
Among various pollutants in drinking and wastewaters, inorganic species are major, and difficult to remove because of smaller size, low concentration and competition with nontoxic species. In this work, various activated carbons have been prepared by phosphoric acid activation from oil palm and coconut shells to study the effect of preparation variables and metal removal capacity. Characterizations were done for the observation of surface area, pore development, textural structure, surface functional groups and its acidity. Thus preparation was customized for carbon with high surface area and wider micro- and mesopores, suitable for removing metal ions. Modification was conducted by dispersing hydrated iron-oxide onto carbon for selective removal of arsenic. Application was tested through batch adsorption in single, binary and ternary solutes solutions and fitting the equilibrium data to various equilibrium and kinetic models. Prepared carbons show very high adsorption capacities for borderline and soft metal ions, copper(II) (25 mg.g-1), nickel(II) (20 mg.g-1), zinc(II) (10 mg.g-1), and lead(II) (75 mg.g-1), compared to that of commercial ones. Adsorption in binary solution shows that hard cation, calcium(II) is not at all competent to borderline cations while the mechanism is assessed as inner-sphere complexation. For low concentration range, ternary-solute adsorption shows the following selectivity order, Ni(II) = Pb(II) = Cu(II). Adsorption capacity of prepared activated carbon for Cr(VI) is saturated at 46 mg.g-1. Although the adsorption capacity of commercial activated carbon dramatically decreases with the lowering of initial solute concentration, it shows a higher monolayer adsorption capacity (71 mg.g-1). The modification significantly enhances the adsorption capacity for As(III) (1.5 mg.g-1) and As(V) (1.0 mg.g-1) than that of parent carbon. The developed activated carbons and modified adsorbents are expected to be useful in removing borderline and soft metal ions as well as ionic or nonionic soft ligands of metalloids present in drinking and wastewaters.